Notes on Aulocera pygmaea (Holik, 1949) and its related taxa (Lepidoptera, Nymphalidae, Satyrinae) - Lang, Song-Yun; Huang, Si-Yao (Zootaxa, 2023)
In this paper, Aulocera pygmaea (Holik, 1949) and its related taxa from W. China (S. Gansu, N. Sichuan, N.W. Yunnan, S.E. Tibet) and N. Myanmar (N. Kachin) are studied. The specific status of A. pygmaea (Holik) is confirmed based upon examining the syntype series. Aulocera atuntsensis (Gross, 1959), A. melanoleuca Sakai, Aoki & Yamaguchi, 2001 stat. nov., and A. auloceroides (H. Huang, 1999) are raised or restored to specific rank rather than treated as subspecies of A. pygmaea (Holik), as in Lang (2021). The lectotype for Satyrus sybillina pygmaea Holik, 1949 is designated. Other related taxa are also discussed.